Survey on Tunisian Dentists' Anti-Inflammatory Drugs' Prescription in Dental Practice. (31st January 2021) - Berhouma, Line; Besbes, Amira; Chokri, Abdellatif; Selmi, Jamil
Abstract : Dentists prescribe several types of drugs such as anti-inflammatory medicines in their practice in order to manage pain. An adequate knowledge of anti-inflammatory drugs' characteristics is mandatory for a reasonable prescription to ensure patients safety. The study aimed to describe dentists' anti-inflammatory drugs prescription in dental practice. Materials and Methods . This study was conducted on independent practice dentists working in the region of Tunis. A questionnaire was made on "Google forms" and sent to all of them via personal emails. The questionnaire included demographic data and 13 questions about anti-inflammatory medicines: indications and contraindications, the side effects, and their prescription in dental practice. Data analysis was performed on SPSS software version 20.0 (trial version), using the χ 2 test for statistical analysis. Results . Two hundred dentists participated to the survey. The female gender was predominant (70%). More than half of the responders were recently graduated and working in their own dental offices. The present study showed that 60% of dentists rarely prescribe anti-inflammatory drugs. Ibuprofen was prescribed by 82% of the dentists. Next came dexamethasone acetate (68.2%). The most frequent indication was postoperative pain (65%). Gastric problem was found to be the most mentioned adverse effect (69%). Thus, 72% of the dentists prescribed proton pump inhibitors with AI. Conclusion . According to this study, dentists have a lack of knowledge and awareness about some contraindications, side effects, and drugs interactions. Thus, knowledge updating, practices assessment, and continuous education are always required to avoid drug iatrogenesis.